Analysis of anxiety in pediatric dentistry context: additional contribution to the validation of the CFSS-DS questionnaire for the Portuguese population - Seabra, Eduardo Manuel Morgado (2024)
Trabalho Final do Mestrado Integrado em Medicina Dentária apresentado à Faculdade de Medicina